A STUDY ON ECONOMIC DAMAGE FOR TOURISM IN KYOTO CITY BY EARTHQUAKE DISASTER - Cui, Mingji; Cui, Qinglin; Toyoda, Yusuke; Kanegae, Hidehiko (ASEAN Journal on Hospitality and Tourism, 2014)
As a typical historic and touristic city of Japan, Kyoto City with a total of 14 UNESCO world heritage sites, and more than 2,000 shrines and temples, attracts annually about 50 million tourists from Japan and overseas. However, because of the disaster of the Great Hanshin-Awaji Earthquake in 1995 and the Great East Japan Earthquake in 2011 which both gave serious damage to Japan, the tourism sector of Kyoto City was impacted by the obvious decrease in the number of tourists. In this study focusing on the two disaster cases of Kyoto City, we estimated the amount of economic damage to the tourism sector, which consists of direct damage from decreasing tourism activities and indirect damage from influences on the regional economy caused by decreases in tourism consumption, which was estimated by the input-output analysis. Then from the analysis of decreasing tourists and estimation of the results, we considered factors whichhave impacted tourism activities and the regional economy.